2008
DOI: 10.1016/j.jallcom.2007.01.138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of activated alloys on hydrogen discharge kinetics of MgH2 nanocrystals

Abstract: Effect of activated alloys on hydrogen discharge kinetics of MgH₂ nanocrystals AbstractActivated alloys synthesized by arc-melting were examined as catalysts for improving the hydrogen sorption characteristics of nanostructured magnesium hydride, proposed as a reversible hydrogen storage material. The MgH 2 -catalyst absorbing materials were prepared by ball milling of pure MgH 2 with hydrided Zr 47 Ni 53 ,Zr 9 Ni 11 , and other investigated alloys. The nanostructured MgH 2 -intermetallic systems were tested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 14 publications
7
21
0
Order By: Relevance
“…Thereby, the energy from ball milling has been probably used to form a new phase instead of reducing the particle size. Similar effects on hydrogenation properties of MgH 2 powders have also been observed by employing other Ni-rich alloys [11].…”
Section: Pcis Ofsupporting
confidence: 76%
See 1 more Smart Citation
“…Thereby, the energy from ball milling has been probably used to form a new phase instead of reducing the particle size. Similar effects on hydrogenation properties of MgH 2 powders have also been observed by employing other Ni-rich alloys [11].…”
Section: Pcis Ofsupporting
confidence: 76%
“…However, it is more difficult to improve the desorption kinetics, and it has been mostly investigated at high temperatures (≥280 • C). More recently, Dehouche et al [11] reported that activated Zr Ni alloys have significant effect in enhancing the desorption kinetics of ball milled MgH 2 at 250 • C. Moreover, a remarkable improvement in desorption kinetics of ball milled MgH 2 at 200 • C under vacuum was also reported by Kojima et al [12] using nano-Ni/Al 2 O 5 /C catalysts composite.…”
Section: Introductionmentioning
confidence: 84%
“…At high temperatures, T ≥ 523 K, the ratio between absorption and desorption equilibrium pressures in films becomes essentially the same as in bulk [3,26], i.e., P abs /P des ≈ 2, proving that thin film optical results are in line with the bulk volumetric data. At lower temperatures (T < 423 K) the difference in hysteresis between thin films and bulk becomes much more pronounced.…”
Section: Hysteresis Behavior and Stress-strain Analysis Of Mg/ta/pd Tsupporting
confidence: 53%
“…The enthalpy of hydride decomposition, −71.0 ± 4.2 kJ/molH 2 , is relatively close to the electrochemistry data, but in a disagreement with the hydrogenography. [3] and MgH 2 -V 3at.%-Ti 2at.% [26], thin [24] and thick MgH 2 films [25] are shown for comparison. Red diamonds are the calculated absorption and desorption equilibrium pressures from the Van't Hoff equation using Pedersen [22] and Stampfer [11] thermodynamic parameters, respectively.…”
Section: Hydrogenography Experiments On Mg/ta/pd Filmsmentioning
confidence: 99%
“…Dehouche et al observed that MgH 2 ball-milled with some Zr-Ni alloys exhibited an improved a/d kinetics, which also depended on the stoichiometry of the alloy [11]. More precisely, the eutectoid composition Zr 36 Ni 64 formed by the two crystalline phases Zr 7 Ni 10 and Zr 8 Ni 21 [12] showed a faster kinetics than Zr 7 Ni 10 and Zr 9 Ni 11 .…”
Section: Introductionmentioning
confidence: 99%